02 Poetry Explained - How Personal Experience and Background Knowledge Help us Make Sense of Poetry - Ezra Pound - Anca STRĂTEANU (Association of Social and Educational Innovation, 2014)
When reading literary texts, we have to be aware of the fact that each reader of a certain text will get a different meaning out of it. It is a nonsense to ask of readers to get the exact same meaning because we cannot possibly know what the author had in mind when he wrote the text and we make sense of everything, especially poetry, through our own personal life experience. Meaning "occurs within and by means of complex systems of codes derived from and determined by human culture". In order to understand a text, which is open, incomplete, insufficient, we have to make use of our imagination and background knowledge to decipher the codes. The reader's task is "to draw out of the work the full complexity of meanings pre-packaged within it". Thus the emphasis of poetics shifts from the "work of art" to the "work of interpretation" which creates the poem from the poem's primary material. The reader's imagination has to fill in the gaps in the text the author left for us, gaps which wait to be filled with meaning and which make us, the readers, become active and creative agents of deciphering codes. Once put on paper, "the work of art never comes to rest". With every reading, a new meaning will be found. With every reader, a range of new meanings will be found. But even more so, with every new reading by the same reader, especially over years, new meanings will be found. How does this happen? you might ask. Through life experience and background knowledge.